Escape plan [videorecording (DVD)] - Schwarzenegger, Arnold; Stallone, Sylvester; Caviezel, Jim, 1968-; Neill, Sam; Jones, Vinnie, 1965- (Summit Entertainment, 2014)
Ray Breslin, one of the world's foremost authorities on structural security, agrees to take on one last job: breaking out of an ultra-secret, high-tech facility called The Tomb. Deceived and wrongly imprisoned, Ray must recruit fellow inmate Emil Rottmayer to help devise a daring, nearly impossible plan to escape from the most protected and fortified prison ever built.